Produção de compostos de aroma por Kluyveromyces marxianus utilizando resíduo de graviola (Annona muricata L.) - Leal, Ana Lúcia de Jesus (2012)
Brazil is a leading global producer of fresh fruits. The production of this food generates a large amount of waste represents a serious problem in the disposal and economic loss associated with non-use of such material. The economic loss of biomass can be reduced by the use thereof in fermentation for the production of aroma compounds. Given that the objective of this study was to evaluate the potential of the waste from the processing to obtain soursop aroma compounds, especially 2-phenylethanol and 2-phenethyl acetate in submerged fermentation by Kluyveromyces marxianus. Preliminary tests were performed to select the residue with the greatest potential for production of these compounds, it was used for both the technique of chromatography and sensory analysis. Among the residues studied (acerola, mangaba and soursop) the soursop has provided a greater potential for the production of aroma compounds of high added value. That done, he was chosen two fruit aroma compounds, 2-phenylethanol and 2-phenethyl acetate, to study the best parameters in order to get more output. First, we evaluated the production of such compounds by means of conducting an experiment, studying six parameters: concentration of sugar, yeast extract, residue of inoculum, pH and agitation. Given the outcome was decided to continue studying the concentration of yeast extract and glucose as well as agitation. Therefore, we used the full factorial design with three dependent variables: sugar concentration ranged from 10 to 50 g/L, yeast extract concentration ranging from 0 to 10 g/L and agitation which ranged from 75 to 150rpm. According to the analysis of the response surface, the production processes of the compounds has been optimized, the conditions proposed, where the increased production of 2-phenethyl acetate may be obtained at concentrations of yeast extract, 2.5 to 7.0 g/L yeast extract, glucose from 21 to 40 g/L an stirred between 95 and 135 rpm and increased production of 2-phenylethanol compound can be obtained at concentrations of yeast extract, between 4.0 and 6.0 g/L of extract of yeast, glucose 22 to 42 g/L and agitation from 100 to 120 rpm.